Analisis Penerapan Stroke Prevention Checklist Untuk Mencegah Re–Attack Stroke - Vione Deisi Oktavina Sumakul; Brigita Maria Karouw (Jurnal SMART Keperawatan, 2025)
Introduction: Stroke occurs when a blood vessel in the brain is blocked or ruptured. This prevents the brain from getting blood and oxygen, causing brain cells to die. Objective: The purpose of this study was to determine the effect of the stroke prevention checklist on preventing re-attack strokes, using a survey research method, namely using samples from a population and using a questionnaire as an instrument for collecting primary data. Method: The type of quantitative research uses a survey method, cross-sectional design. Sampling uses a non-probability sampling technique and uses 45 samples that are purposive sampling (stroke patients). The instrument in this study uses the prevention checklist format from the American Stroke Association in 2022. The analysis is divided into univariate, namely describing the characteristics of respondents (age, gender, diagnosis) and research variables. Furthermore, bivariate analysis was carried out to see the relationship between the independent variable, namely the stroke prevention checklist, and the dependent variable, namely re-attack stroke, and using the chi square test. Multivariate analysis uses a regression test. Results of the study showed that the application of stroke prevention checklist in preventing recurrent stroke attacks was very effective. The results of the simultaneous test showed that the variable of maintaining a diet was the most effective preventive measure in preventing stroke (p = 0.003). Conclusion: People who have had a stroke have a greater risk of having another stroke, especially if the risk factors are not well managed.